Gender Differences In Self-Inflicted Burns - MS, Cepeda-Diaz (Morressier, 2017)
Introduction:The risk of self-inflicted burns has been described as highly influenced by people's living conditions, lifestyles and culture [1]. These factors partly explain differences observed globally in rates and distribution of burn-related self-inflicted injuries both between and within countries [1,2]. However, little is known about gender differences on preferred methods for these types of injuries, motives, and also gender differences in different cultures. However, healthcare professionals and policy makers could benefit from this knowledge to design tailored effective preventive strategies [3, 4]. Objective:To analyse if gender-related patterns of self-inflicted burns exist and to describe prototypical profiles between males and females. Methods:This cross-sectional study is based on burn case reports (N=51) from an acute specialized burns unit (SBU) from a reference hospital in Catalonia, Spain (2010-2018). Data regarding age, sex, triggers for self-inflicted burns, total burnt surface area (TBSA), methods and circumstances of the injury, and other relevant clinical variables were collected. Results:Mean age of the whole sample was 42,16u00b113,24 and most of them were males (n=38, 74,5%) from Spain (n=37, 72,5%). Approximately half of the sample did not have children (n=24, 55,8%), were single (n=31, 66%), finished elementary education (n=38, 84,4%) and were unemployed (active but not working n=29, 64,5%; retired n=1, 2,2%; unable to work n=4, 5,9%). In 68,6% cases the self-inflicted burn was clearly and autolytic attempt (n=35). Main triggers for the self-inflicted burn were psychopathology (n=20, 48,8%), familial conflicts (n=14, 34,1%), unresolved issues with justice (n=3, 7,3%), problems at work (n=1, 2,2%) or other unspecified causes (n=2, 4,9%). The most prevalent psychopathological diagnosis were bipolar disorder (n=12, 25%), major depression (n=11, 22,9%) and schizophrenia (n=10, 20,8%). Indeed, 90,2% patients (n=46) had psychopathological background and 66,7% (n=34) were still on active psychiatric treatment. Main method was to set fire on own clothes (n=42, 82,4%) at home (n=27, 55,1%) or in public places (n=12, 24,5%). TBA burnt was around 25,86%u00b126,32 and mean stage at the SBU was 32,43u00b130,36 days (range 1-123 days). The number of previous attempts range between 0 and 6 (mean 1,67u00b11,57) and destination at discharge was mainly at home (n=20, 39,2%) or to other acute units/hospitals (n=15, 29,4%). Differences between genders were observed for the intention of the self-inflicted burn with significantly more males presenting these injuries as a clear autolytic attempt (u03c72=4,093, p=0.043).Conclusions:Most patients with self-inflicted burns were men with clear autolytic intentions. Considering the high prevalence of psychiatric disorders among the sample (both gender included), it cannot be concluded that they present higher risk factors compare to females or use more aggressive methods. However, the need of constant psychiatric support even once discharged is clear, because it can be helpful in preventing future episodes of self-harm or suicide. References1.tPeck MD. Epidemiology of burns throughout the World. Part II: Intentional burns in adults. Burns 2012;38(5):630-72.tLalou00eb V. Patterns of deliberate self-burning in various parts of the world. A review. Burns 2004;30(3):207-153.tTitscher A, Lumenta DB, Belke LP, Kamolz LP, Frey M. A new diagnostic tool for the classification of patients with self-inflicted burns (SIB): The SIB-Typology and its implications for clinical practice. Burns 2009;35(5):733-4 4.tLlamaran K, Malaiappan M, Kannan PP, Jagadeesan MS, Jose Mathew, Heber Anandan. Relationship between Psychosocial Stressors and the Intent and Lethality of Suicidal Behavior. Int J Scientif Study 2016,4(7)35-8